2004
DOI: 10.1038/sj.bjc.6601571
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic density and metastatic spread in human malignant melanoma

Abstract: Malignant melanoma (MM), the most common cause of skin cancer deaths, metastasises to regional lymph nodes. In animal models of other cancers, lymphatic growth is associated with metastasis. To assess if lymphatic density (LD) was increased in human MM, and its association with metastasis, we measured LD inside and around archival MM samples (MM, n ¼ 21), and compared them with normal dermis (n ¼ 11), basal cell carcinoma (BCC, n ¼ 6) and Merkel cell carcinoma (MCC), a skin tumour thought to metastasise throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
131
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 27 publications
(27 reference statements)
9
131
4
Order By: Relevance
“…Lymphoscintigraphy enables us to identify and localise the sentinel lymph nodes of primary tumours exhibiting lymphogenic metastatic potential. The findings of Shields et al (2004) now provide immunohistochemical evidence that helps explain the results of our recent prospective lymphoscintigraphic feasibility study on 276 melanoma patients (Maza et al, 2003). We found a relationship between the speed at which sentinel lymph nodes appear on dynamic lymphoscintigraphic scans and their metastatic involvement.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Lymphoscintigraphy enables us to identify and localise the sentinel lymph nodes of primary tumours exhibiting lymphogenic metastatic potential. The findings of Shields et al (2004) now provide immunohistochemical evidence that helps explain the results of our recent prospective lymphoscintigraphic feasibility study on 276 melanoma patients (Maza et al, 2003). We found a relationship between the speed at which sentinel lymph nodes appear on dynamic lymphoscintigraphic scans and their metastatic involvement.…”
supporting
confidence: 64%
“…Several well-documented factors predictive of regional nodal metastasis particularly include tumour ulceration and thickness (Balch et al, 2003). I read with great interest the article of Shields et al (2004), who have proven that lymphatic capillary density can be used to discriminate between melanomas that will subsequently metastasise and ones that will not. Their prognostic index based on immunohistochemically measured lymphatic capillary density in combination with lymphatic invasion and tumour thickness enables clear discrimination between metastatic and nonmetastatic human malignant melanoma.…”
mentioning
confidence: 99%
“…38-40 In human melanoma, increased intra- and peritumoral LVD as well as the lymphatic growth factor VEGF-C strongly correlate with metastatic dissemination. 17 , 33 , 41-43 Lymphatic vessels may support migration of tumor cells, but may also modulate immune cells, as recently demonstrated in primary tumors and draining LNs in mice, 24 , 25 , 44 raising the possibility that lymphatics mediate immune suppression and poor clinical outcome in cancer patients. 19 , 31 , 42 Because corresponding human data are missing, we performed a very wide IHC analysis.…”
Section: Discussionmentioning
confidence: 92%
“…In head and neck cancer, studies show an association of increased LVD and new vessel formation with lymph node metastasis and worse prognosis (Beasley et al, 2002;Maula et al, 2003). In melanoma, one large study with 202 samples demonstrated improved overall and recurrence free survival with increased LVD in both peritumoural and intratumoural areas (Straume et al, 2003) suggesting that vessel density may be a marker for an improved immune response whereas two smaller studies conclude the opposite with intratumoural lymphatics significantly higher in metastatic melanomas and correlating with poor survival (Dadras et al, 2003;Shields et al, 2004). Interestingly, in breast cancer intratumoral lymphatic vessels are absent and the significance of peritumoural vessels is unclear (Williams et al, 2003;Bono et al, 2004;Vleugel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%